Continued Supervision for the Common Pediatric Subspecialty Entrustable Professional Activities May Be Needed Following Fellowship Graduation. (July 2021) - Turner, David A.; Schwartz, Alan; Carraccio, Carol; Herman, Bruce; Weiss, Pnina; Baffa, Jeanne M.; Chess, Patricia; Curran, Megan; Dammann, Christiane; High, Pamela; Hsu, Deborah; Pitts, Sarah; et al.
Abstract : Purpose: Entrustable professional activities (EPAs) are one approach to competency-based medical education (CBME), and 7 EPAs have been developed that address content relevant for all pediatric subspecialties. However, it is not known what level of supervision fellowship program directors (FPDs) deem necessary for graduation. The Subspecialty Pediatrics Investigator Network (SPIN) investigated FPD perceptions of the minimum level of supervision required for a trainee to successfully graduate. Method: In 2017, SPIN surveyed all FPDs of accredited fellowships for 14 subspecialties. For each EPA, the minimum supervision level for graduation (ranging from observation only to unsupervised practice) was set such that no more than 20% of FPDs would accept a lower level. Results: The survey response rate was 82% (660/802). The minimum supervision level for graduation varied across the 7 EPAs from 2 (direct) to 4 (indirect for complex cases), with significant differences between EPAs. The percentage of FPDs desiring a lower minimum supervision level ranged from 3% to 17%. Compared with the 4 nonclinical EPAs (quality improvement, management, lead within the profession, scholarship), the 3 clinical EPAs (consultation, handover, lead a team) had higher minimum supervision graduation levels ( P < .001), with less likelihood that an FPD would graduate a learner below their minimum level ( P < .001) Conclusions: Consensus among FPDs across all pediatric subspecialties demonstrates the potential need for ongoing supervision for graduates in all 7 common pediatric subspecialty EPAs after fellowship. As CBME programs are implemented, processes and infrastructure to support new graduates are important considerations for leaders.